PENGARUH KEPEMIMPINAN, MOTIVASI , PENGEMBANGAN KARIR, PROMOSI JABATAN TERHADAP KINERJA PEGAWAI (Studi Kasus Biro Kesejahteraan Rakyat Kantor Sekretariat Daerah Provinsi Jawa Tengah) - Fatihatul Siyadah, 15.05.51.0039; Waruwu, Penunjang (Students' Journal of Economic and Management, 2019)
The purpose of this study was to determine the effect of Leadership, Motivation, Career Development, and Job Promotion on Employee Performance at the People's Welfare Bureau at the Office of the Regional Secretariat of Central Java Province. This study also aims to jointly influence the four independent variables on the dependent variable and to find out which variables are the most dominant influence among the four independent variables on the dependent variable, the type of research used is qualitative research, with an employee population of 60 employees. Data collection uses a questionnaire with a Likert scale. Based on the calculation of SPSS 19 from the t test on leadership variables obtained significance of 0.017> 0.05, Ho is rejected and Ha is accepted, significance motivation variable is 0.380> 0.05, Ho is accepted and Ha is rejected, career development variable is obtained significance 0.066 <0.05 then Ho is accepted and Ha is rejected, the promotion promotion variable is obtained significance of 0.121> 0.05, Ho is rejected and Ha is rejected. The results of the f test show that it affects the dependent variable together. The results of the coefficient of determination obtained a value of 0.309 means that the variables of leadership, motivation, career development, and promotion can explain employee performance 30.9% and the rest influenced by other variables not found in this study.